STEM education impact on the development of primary school students' meta-subject skills: an experimental study in Kazakhstan - Yesnazar, Asel; Zhorabekova, Ainur; Kalzhanova, Altynai; Abilkhairova, Zhanar; Ortaeva, Kamila; Jumassaeva, Zhuldyz (Frontiers in Education, 2025)
IntroductionOrganizing the primary education process within the framework of STEM education enhances students' scientific literacy, fosters the development of engineering skills, promotes analytical and critical thinking abilities, and increases interest in technical disciplines. This study is grounded in an integrative approach to organizing the primary education process through STEM education, focusing on the development of meta-subject skills in primary school students. Based on this integrative approach, a dedicated STEM-oriented educational program was developed.MethodsThe study was conducted in three stages: diagnostic, formative, and control. A pre-test and post-test design was employed to compare the outcomes of the control and Experimental classs. The Experimental class was taught using the newly developed STEM program, while the control class followed the traditional curriculum.ResultsAll data were analyzed using the Mann–Whitney U test. The Shapiro–Wilk test was employed to assess the normality of data distribution. The pre-test results indicated that the initial knowledge levels of the two classes were comparable. However, the post-experimental findings revealed significant changes. A statistically significant difference was identified between the performance of the control and experimental classes, with the experimental class demonstrating superior outcomes. These results provide clear evidence of the effectiveness of the interventions implemented in the Experimental class. Overall, the findings confirm the reliability and validity of the study.DiscussionThe STEM-based educational program was tested during the experiment, and its effectiveness was evaluated through a comparative analysis of pre- and post-test results. The findings provide strong evidence in support of the effectiveness of the instructional approach applied to the Experimental class.